The Role of the Deroduwur Community Towards Al-Asy'ariyyah Wonosobo One-Stop Islamic Religious Education Institution - Moh Sakir; Robingun Suyud El Syam; Rifqi Muntaqo (AL-ISHLAH: Jurnal Pendidikan, 2022)
The Law on the National Education System No. 20 of 2003 confirms that education is a shared responsibility between the government, the community and the family. So the community must be involved in the implementation of education. Through a qualitative descriptive approach, the research concludes; that the role of the Deroduwur community in the one-roof educational institution Al-Asy'ariyyah, has at least four components: increasing student distribution, participating in creating a religious school environment, involvement in school committees, and promotion of schools through alumni forums. This finding reinforces the fact that society and schools cannot be separated, the synergy of the two has an impact on increasing the quality and quantity of education.